A Collection of Service Time Distributions Parameters Study and Impact in M|G|∞ System Busy Period and Busy Cycle Length Distributions - Ferreira, M. A. M. (EasyChair Preprint Nº 8213, 2025)
We present the problems that arise when calculating the moments of service time probability distributions for which the M|G|∞ queue system busy period and busy cycle-an idle period followed by a busy periodlength probability distributions become very easy to study and show how to overcome them. We also, calculate the renewal function, the “peakedness,” and the “modified peakedness” for the M|G|∞ busy period and busy cycle length in the case of those service time distributions.